Mechanical simulation of li-ion cells and derivation of state of safety function - Li, Zheng Bo (2016)
In this thesis different experiments are conducted to characterize the mechanical behavior of lithium ion cells. Compression and indentation of cells in pouch and 18650 formats was conducted. The suitable experiment setups for each test were designed. The rate dependency of pouch cells through a normal compression was observed. The difference of mechanical behavior of cells with different active material was discussed. A relationship between peak load and internal short circuit of pouch cells under indentation was concluded. Calibration and verification of 3D finite element simulation models was discussed. The simulation of compression and indentation of different types of cells were done. A good correlation of load-displacement was obtained in some cases, but not for all cases. A state of safety function was developed in terms of pressure behavior of a pouch cell.